2012
DOI: 10.1007/s10995-012-1061-4
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Evaluation of the Choice of Traditional Birth Attendants for Maternity Care in 2008 Sierra Leone: Implications for Universal Skilled Attendance at Delivery

Abstract: Maternal and newborn death is common in Sierra Leone; significant reductions in both maternal and newborn mortality require universal access to a skilled attendant during labor and delivery. When too few women use health facilities MDGs 4 and 5 targets will not be met. Our objectives were to identify why women use services provided by TBAs as compared to health facilities; and to suggest strategies to improve utilization of health facilities for maternity and newborn care services. Qualitative data from focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 10 publications
5
40
1
Order By: Relevance
“…Previous studies in Africa have demonstrated clearly the relationship between mistreatment and future childbirth in health facilities. 13,27,28 Eliminating all forms of mistreatment and ensuring that women's rights are respected hinges on extensive education, especially in low resource settings, on whether such acts are appropriate or useful. In this study, some women believed that in some contexts, some forms of physical and verbal abuse are needed to ensure the safety of the mother and baby during childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Africa have demonstrated clearly the relationship between mistreatment and future childbirth in health facilities. 13,27,28 Eliminating all forms of mistreatment and ensuring that women's rights are respected hinges on extensive education, especially in low resource settings, on whether such acts are appropriate or useful. In this study, some women believed that in some contexts, some forms of physical and verbal abuse are needed to ensure the safety of the mother and baby during childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…While there are global efforts to increase facility-based childbirth, there are significant barriers in some settings, preventing women from attending facilities, including distance [13, 14], cost [15, 16], and perceived quality of care [15, 17, 18]. More recently, improving quality of care, including women’s experiences of care, has been highlighted as a key component of strategies to further reduce preventable maternal mortality and morbidity [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies conducted in Sierra Leone identified prohibitive costs to be one of the main barriers for women accessing maternal health care and utilising facilities during childbirth [ 15 - 17 ]. In 2010, in response to these findings, the government of Sierra Leone introduced the Free Health Care Initiative (FHCI) for pregnant women, breastfeeding mothers and children under the age of 5 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%